2016
DOI: 10.1177/0308022615627176
|View full text |Cite
|
Sign up to set email alerts
|

Return-to-work support for employees with mental health problems: Identifying and responding to key challenges of sick leave

Abstract: Introduction: This research explored return-to-work and sick leave experiences of workers with mental health issues in contact with acute or community mental health services. Method: Using a critical realist methodology with a comparative case study and collaborative design, 21 employed participants recovering from mental health problems participated in semi-structured interviews. Data were analysed using inductive and deductive thematic and constant comparative analysis. Findings: While on sick leave, despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 19 publications
4
19
0
1
Order By: Relevance
“…That study proposed a new concept, occupational capital, highlighting the occupational dimension in public health areas such as the sick leave process. In this sense, occupational capital is defined as a combination of external opportunities and support for occupational performance and the internal capacities to access this [44]. This is in accordance with the results of our study, where keeping up meaningful, everyday occupations leads to feelings of competence and importance.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…That study proposed a new concept, occupational capital, highlighting the occupational dimension in public health areas such as the sick leave process. In this sense, occupational capital is defined as a combination of external opportunities and support for occupational performance and the internal capacities to access this [44]. This is in accordance with the results of our study, where keeping up meaningful, everyday occupations leads to feelings of competence and importance.…”
Section: Discussionsupporting
confidence: 89%
“…This is in accordance with the results of our study, where keeping up meaningful, everyday occupations leads to feelings of competence and importance. Adding a focus on participation in everyday occupations could thereby be proposed to support recovery against a more resilient worker-role [44]. In addition, such a focus is also compatible with findings from another study [45], where coping-developing interventions were found to have an impact on work ability as well as other everyday activities.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Des répercussions négatives sur la santé sont également présentes chez les personnes qui ont un emploi, mais qui se retrouvent en arrêt de travail prolongé en raison d'un trouble mental. Parmi ces répercussions négatives, il y a le fait de se sentir isolé et désoeuvré en l'absence de l'effet structurant associé à la routine de travail 14 , ainsi que de ressentir un niveau élevé de honte 15 . À cet égard, les personnes en arrêt de travail en raison d'un trouble mental seraient de quatre à cinq fois plus à risque de ressentir un niveau modéré à élevé de honte par rapport à tout autre trouble de santé.…”
Section: Pourquoi Soutenir Le Rat Après Un Arrêt De Travail Consécutiunclassified
“…Two qualitative studies examined established workers diagnosed with mental illness or a psychiatric disorder. Cameron et al (2016) explored the experiences of being on sick leave among people with severe mental illnesses. The results showed how much people treasured their work identity, and how potentially damaging sick leave can be to those that benefit from the structured routines and social interaction that employment provides.…”
mentioning
confidence: 99%